Big Data Analytics in Smart Power Systems: A Survey Paper - Ahmad, Farhan (UMT Artificial Intelligence Review, 2021)
In recent years, technology has brought us many advancements. One of them is integrating big data with smart grid/smart power. In this study, a scientific approach used to help the power system is studied. Additionally, with the help of previously published literature, different survey papers are reviewed to investigate the key challenges of integrating Big Data Analytics (BDA) with smart grid. Subsequently, BDA characteristics are also studied. Next, data analysis techniques and BDA applications in the domain of smart grids are studied. It is followed by a section discussing techniques such as Hadoop and Spark. Their framework is also briefly examined in order to know about their working. The last section provides a conclusion and future directions. KEYWORDS: advanced metering infrastructure (AMI), applications of big data, big data analytics (BDA), data architectures, data mining, data privacy, data security, data uncertainty, data volume, hadoop, spark, Vz of the data, smart grid, smart power system big